Body composition, blood pressure and cardiorespiratory functional capacity in elite athletes - Durmic, T.; Djelic, M.; Lovic, D.; Gavrilovic, T.; Cirkovic, A.; Zdravkovic, M. (Science & Sports, 2017)
Objectives: Regular endurance training in athletes is associated with a higher maximal oxygen uptake (VO2max), a lower body fat percentage (BF%), and improved blood pressure (BP) control. However, are those adaptive changes present in athletes with higher BF%, has not been previously examined. This study aimed to evaluate the influence of the body composition to the resting and maximal BP values and cardiorespiratory functional capacity in elite athletes. Equipment and methods: A total of 194 men elite athletes were examined. According to World Health Organization recommendation, athletes were divided according to BF% in 3 groups: low: = 8, optimal: 9-19%, overweight: = 20%. Anthropometric measurements, resting systolic (SBP) and diastolic (DBP) pressures were measured. VO2max and maximal BP were directly measured by maximal graded exercise test on treadmill until exhaustion. Results: Seventy-six (39%) athletes had low BF%, 107 (55%) had optimal BF%, while 11 (5%) athletes had BF% in overweight category. The incidence of hypertension (SBP = 140 and/or DBP = 90 mmHg) was 4% in low BF%, 6% in optimal and 21% in the overweight group. Athletes in overweight category had significantly higher resting SBP and DBP values, and maximal DBP and lower VO2max compared to all other athletes (P < 0.001). Recovery DBP was significantly lower in low BF% group compared to all other athletes (P < 0.01). There was statistically significant negative correlation between resting SBP and VO2max values in normal BF% group (r = -0.24; P < 0.001). BF% independently predicted resting BP and HR, as well as maximal DBP and VO2max, while BMI independently predicted only maximal HR and resting DBP (P < 0.001). Optimal body composition in athletes is a strong determinant of optimal functional aerobic capacity and resting BP. BF% elevation is strong negative predictive factor for maximal oxygen uptake and resting BP.